Do new first year students seek optimal distinctiveness in a new learning environment?. Issue 2 (July 2019) - Pownall, Ian; Kennedy, Victoria; Acquaye, David
Abstract: The learning experience of the first year student joining Higher Education Institutions (HEI) can be examined from a number of perspectives and we focus upon the development of identity within that new learning environment. A conceptual framework is presented to argue that the tension between distinctiveness and social identification of the learner with the environment, contributes to how the learner engages in that environment through their processing style. A supporting empirical analysis explores this argument for a small sample of new first year students in two UK HEIs studying business modules. We determine that students exhibit cognitive dissonance through exercising a dominant processing style that is not primarily seeking to identify with that learning environment whilst also recognising the benefits of a more engaged processing style aligned with greater identification with their peer group. We propose therefore there is a need for the development of social identification capacity within new students. Highlights: Four styles of information processing describe the scope learner engagement. Four styles of information processing extend the literature in this area. Optimal distinctiveness theory contributes to information processing style choice. Surveyed students exhibited an information processing style that preserved existing identities. Surveyed students also exhibited cognitive dissonance in the conflicting views they held and processing styles used.